Molecular analysis of microbial community structures in Nigerian oil production and processing facilities in order to access souring corrosion and methanogenesis. (February 2016) - Okoro, Chuma; Ekun, Oluseye A.; Nwume, Michael I.; Lin, Johnson
Highlights: Pyrosequencing surveys in samples of Escravos and Meren facilities were examined. The sulfate reducing and nitrate reducing bacteria activities were higher in Escravos. The sulfate reducing and acid producing bacteria counts were also higher in Escravos. The corrosion rates were higher in Escravos with higher methane productions. Escravos samples had high fractions of bacteria and methanogenic Archaea. Abstract: Microbial communities associated with corrosion in samples from Nigeria facilities were examined. The SRB, heterotrophic nitrate reducing bacteria activities and SRB and acid producing bacteria counts were higher in Escravos than those in Meren. The corrosion rates were also higher in the Escravos samples possessing higher capacity in methane production. Pyrosequencing surveys indicate that Escravos samples had high fractions of potential hydrocarbon degrading bacteria and methanogenic archaea (mainly Methanosaeta and Methanococcus ). Microbial activities at Meren were dominated by bacteria ( Marinobacterium, Halomonas, Pseudomonas and Kosmotoga spp.). The research was the first to analyze microbial community structures in the oil facilities investigated.